2002
DOI: 10.1038/sj.onc.1205107
|View full text |Cite
|
Sign up to set email alerts
|

Repression of in vivo growth of Myc/Ras transformed tumor cells by Mad1

Abstract: The Myc/Max/Mad network of transcriptional regulatory proteins plays an essential role in cell proliferation, growth, apoptosis, and di erentiation. Whereas Myc proteins a ect cell cycle progression positively, Mad proteins are negative regulators of cell proliferation. It has been shown in several in vitro systems that Mad proteins antagonize c-Myc functions. In this report we describe the inhibition of tumor cell outgrowth in vivo by Mad1 expression. Transformed cell lines were generated by co-transfection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 65 publications
1
20
0
Order By: Relevance
“…Mxi1-SR␤ has been shown to inhibit proliferation of prostate carcinoma and glioblastoma cell lines when overexpressed (67,73). Similarly, Mad1 overexpression inhibits proliferation in different cell lines (31,57) and blocks Myc/Ras-dependent tumor formation (11).…”
Section: Discussionmentioning
confidence: 99%
“…Mxi1-SR␤ has been shown to inhibit proliferation of prostate carcinoma and glioblastoma cell lines when overexpressed (67,73). Similarly, Mad1 overexpression inhibits proliferation in different cell lines (31,57) and blocks Myc/Ras-dependent tumor formation (11).…”
Section: Discussionmentioning
confidence: 99%
“…Since the oncogene-transfected REC cultures were replated at a defined cell number, immediate effects of the survivin-antisense construct on cellular viability did not bias the results. Thus, the proven cooperation of cmyc with c-H-ras in primary REC (Land et al, 1983;Cerni et al, 1995Cerni et al, , 2002Simonitsch et al, 2001) was hampered by reduced amounts of endogenous survivin. We are currently investigating whether survivin is also important for other oncogene cooperation models.…”
Section: Discussionmentioning
confidence: 99%
“…A rare c-H-ras-only transformed cell line (R-1) was also included in the analysis, and normal, nontransfected rat embryo cells (RECs) served as control. Expression of transgenes was verified by Northern-and Western blot analysis (Cerni et al, 1990(Cerni et al, , 1995(Cerni et al, , 2002; and data not shown).…”
Section: Survivin Is Elevated In C-h-ras Expressing Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we identified a first nsSNP in mitotic-arrest-deficient MAD-1 protein, a transcriptional repressor of MYC target genes, and another in the product of one of the MYC target genes, namely the translation initiation factor eIF-2. Translation initiation factor IF-2 was shown to be involved in transformation when its function is upregulated (Rosenwald et al, 1993;Rosenwald, 1996), while MYC antagonist MAD-1 acts as a tumour suppressor in a variety of cell lines (Ayer et al, 1993;Roussel et al, 1996;Cerni et al, 2002). Notably, the Arg to His change at position 558 identified in the MAD-1 protein has also been reported as an uncommon polymorphism in a case study of lung cancer (Nomoto et al, 1999).…”
Section: Association With Tumour Developmentmentioning
confidence: 99%